Gondra's Exploration of Tube Volume - Juraganda S, Chandra Saptanto; Tambunan, Hardi; Simanjuntak, Ruth M (Jurnal Ilmiah Mandala Education (JIME), 2025)
This study aims to explore students' understanding of the concept of cylinder volume through a contextual approach based on the fictional character "Gondra". Gondra is used as a character in story problems that are used as a medium to attract attention and improve students' understanding of mathematical concepts. Using a descriptive qualitative approach, data were collected through observations, interviews, and written tests of sixth-grade elementary school students. The results of the study indicate that a narrative-based approach with the character Gondra is able to improve students' understanding in determining the volume of a cylinder conceptually and procedurally. This study also shows a higher emotional involvement of students in solving contextual mathematical problems.